Coexistence of Gilbert Syndrome and Hereditary Spherocytosis in a Child Presenting with Extreme Jaundice - Lee, Jae Hee; Moon, Kyung Rye (Pediatric gastroenterology, hepatology & nutrition, 2014)
Gilbert syndrome is the most common inherited disorder of bilirubin glucuronidation. It is characterized by intermittent episodes of jaundice in the absence of hepatocellular disease or hemolysis. Hereditary spherocytosis is the most common inherited hemolytic anemia and is characterized by spherical, osmotically fragile erythrocytes that are selectively trapped by the spleen. The patients have variable degrees of anemia, jaundice, and splenomegaly. Hereditary spherocytosis usually leads to mild-to-moderate elevation of serum bilirubin levels. Severe hyperbilirubinemia compared with the degree of hemolysis should be lead to suspicion of additional clinical conditions such as Gilbert syndrome or thalassemia. We present the case of a 12-year-old boy with extreme jaundice and nausea. The diagnosis of hereditary spherocytosis was confirmed by osmotic fragility test results and that of Gilbert syndrome by genetic analysis findings.